Competition for promotion can induce household specialization between equally competitive spouses - Spencer Bastani; Lisa Dickmanns; Thomas Giebe; Oliver Gürtler (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
We analyze equally competitive spouses competing for promotion in their respective workplaces and show that an asymmetric equilibrium featuring household specialization can arise. Examples where the asymmetric equilibrium is welfare-superior to the symmetric equilibrium are highlighted. By investing heavily in the career of only one spouse, families reduce the intensity of the rat race of the working environment and obtain less risky consumption opportunities. Our findings suggest that specialization can reflect an efficient response to the competitiveness of the labor market and may arise even when all workers have equal opportunities to succeed in the labor market.
Keywords: C72; D13; J16; J71; M51; M52; 330; contest theory; gender equality; family; household; competition